2001
DOI: 10.1038/sj.bmt.1702835
|View full text |Cite
|
Sign up to set email alerts
|

Skin involvement as the first manifestation of systemic aspergillosis in patients after allogeneic hematopoietic cell transplantation

Abstract: Summary:Skin involvement due to a systemic infection with Aspergillus species in the course of allogeneic hematopoietic cell transplantation is extremely rare. We report the clinical course of two patients with hematologic malignancies who underwent allogeneic hematopoietic cell transplantation (HCT) and developed disseminated skin involvement as the first clinical symptom of a proven systemic Aspergillus infection. Bone Marrow Transplantation (2001) 27, 753-755. Keywords: cutaneous Aspergillus infection; HCT;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Besides, the immune status of the infected patient should be evaluated as the host underlying immunity plays a critical role in the treatment of aspergillosis. [ 6 ] Schimmelpfennig et al [ 7 ] reported a case in which aspergillosis developed and progressed in a patient with chronic myeloid leukemia despite prompt therapy with amphotericin B. Resistance testing of Aspergillus fumigatus isolated from the lesion against amphotericin B showed that this species is fully sensitive to amphotericin B in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the immune status of the infected patient should be evaluated as the host underlying immunity plays a critical role in the treatment of aspergillosis. [ 6 ] Schimmelpfennig et al [ 7 ] reported a case in which aspergillosis developed and progressed in a patient with chronic myeloid leukemia despite prompt therapy with amphotericin B. Resistance testing of Aspergillus fumigatus isolated from the lesion against amphotericin B showed that this species is fully sensitive to amphotericin B in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Later in the course of the disease, these lesions evolve into black eschars. The skin lesions present in our patient resolved within days of initiation of antifungal regimen [12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic chemotherapy within a month of death is a risk factor associated with dissemination [97]. As mentioned, skin lesions may be the first clinical manifestation and may lead to the diagnosis [98]. Uncommon manifestations of disseminated aspergillosis include endophthalmitis [99], empyema, arthritis [100], intestinal infarction [101] and thyrotoxicosis [102].…”
Section: Disseminated Aspergillosismentioning
confidence: 99%